Protective Mechanisms of S. lycopersicum Aqueous Fraction (Nucleosides and Flavonoids) on Platelet Activation and Thrombus Formation: In Vitro, Ex Vivo and In Vivo Studies. (16th September 2013) - Fuentes, Eduardo; Pereira, Jaime; Alarcón, Marcelo; Valenzuela, Claudio; Pérez, Pablo; Astudillo, Luis; Palomo, Iván
Abstract : The purpose of this research was to investigate mechanisms of antiplatelet action of bioactive principle from S. lycopersicum . Aqueous fraction had a high content of nucleosides (adenosine, guanosine, and adenosine 5′-monophosphate) by HPLC analysis. Also aqueous fraction presented flavonoids content. Aqueous fraction inhibited platelet activation by 15 ± 6% (P < 0.05 ). Fully spread of human platelets on collagen in the presence of aqueous fraction was inhibited from 15 ± 1 to 9 ± 1  μ m 2 (P < 0.001 ). After incubation of whole blood with aqueous fraction, the platelet coverage was inhibited by 55 ± 12% (P < 0.001 ). Platelet ATP secretion and aggregation were significantly inhibited by the aqueous fraction. At the same concentrations that aqueous fraction inhibits platelet aggregation, levels of sCD40L significantly decreased and the intraplatelet cAMP levels increased. In addition, SQ22536, an adenylate cyclase inhibitor, attenuated the effect of aqueous fraction toward ADP-induced platelet aggregation and intraplatelet level of cAMP. Platelet aggregation ex vivo (human study) and thrombosis formation in vivo (murine model) were inhibited by aqueous fraction. Finally, aqueous fraction may be used as a functional ingredient adding antiplatelet activities (nucleosides and flavonoids) to processed foods.